Recovery from forward masking in elderly cochlear implant users - Lee, Edward R; Friedland, David R; Runge, Christina L (Otology & neurotology, 2012)
To compare temporal aspects of peripheral neural responses and central auditory perception between groups of younger adult and elderly cochlear implant users. Cohort study. Academic hospital and cochlear implant center. Adult cochlear implant users aged 28 to 57 years in the younger group (n = 5) and 61 to 89 years (n = 9) in the elderly group. All subjects used Advanced Bionics devices. Diagnostic. Time constants of neural (i.e., electrically evoked compound action potentials [ECAPs]) and perceptual recovery from forward masking. Interstimulus intervals (ISIs) were varied in both experiments. ECAP recovery rates were equivalent between groups, and no correlation was found between ECAP recovery and age. No correlations were found between ECAP recovery and speech perception. Psychophysical recovery was significantly slower in the elderly compared with the younger subjects (p < 0.0005), with a significant effect of age (R2 = 0.70, p < 0.0005). At the longest ISI (240 ms), elderly subjects experienced a mean maximum threshold shift of 35.2% (relative to 1 ms ISI) versus 14.8% for younger subjects. There was a significant positive relationship between psychophysical recovery and consonant-nucleus-consonant word scores (R2 = 0.62, p < 0.001), although no relationship was found with Hearing in Noise Test sentences. These findings suggest that difficulties observed in speech perception by elderly CI users may be due to age-related changes in the central rather than peripheral auditory system. With further study, these results may provide information to allow clinicians to assess patients' temporal processing abilities and facilitate setting program parameters that will maximize their auditory perceptual experience with a cochlear implant.